Uji Aktivitas Antioksidan Ekstrak Etanol Buah Mangsi (Phyllanthus reticulatus) dengan Menggunakan Metode DPPH - wahab, Nurmayada; Muflihunnah, Andi; Rahmawati, Rahmawati (PHARMACY UMI JOURNAL SYSTEM, 2024)
Antioxidants are compounds that can inhibit free radical reactions in the body. Synthetic antioxidants are often used for food but their use is limited because they are toxic. This study aims to determine the antioxidant activity of mangosteen fruit samples. The method used in this test is the DPPH method. This test was carried out by adding 1 mL of the test solution with 4 mL of 40 ppm DPPH. The absorbance was measured with a UV-Vis spectrophotometer at a wavelength of 498 nm and the IC50 value was calculated based on the absorbance data. The calculation results show that there is antioxidant activity in the ethanol extract of mangosteen fruit (Phyllantus reticulatus) with an IC50 value of 2.278 ppm, that is, these results show very strong antioxidant activity, and quercetin as a comparison has a very strong antioxidant activity with an IC50 value of 4.184 ppm. Keywords: : Antioxidant, Ethanol Extract of Mangsi Fruit (Phyllanthu reticulatus), DPPH, Spectrophotometer UV-Vis